2014
DOI: 10.1016/j.aquatox.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated dissolved carbon dioxide and perfluorooctane sulfonic acid, given singly and in combination, on steroidogenic and biotransformation pathways of Atlantic cod

Abstract: In the aquatic environments, the predicted changes in water temperature, pO2 and pCO2 could result in hypercapnic and hypoxic conditions in aquatic animals. These conditions are thought to affect several basic cellular and physiological mechanisms. Yet, possible adverse effects of elevated CO2 (hypercapnia) on teleost fish, as well as combined effects with emerging and legacy environmental contaminants are poorly investigated. In this study, juvenile Atlantic cod (Gadus morhua) were divided into groups and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 120 publications
(112 reference statements)
1
1
0
Order By: Relevance
“…In a previous experiment, Miller et al (2013) observed an increase in reproduction at elevated CO 2 levels similar to those used in this experiment. A similar increase in reproduction has since been documented in the three-spine stickleback (Schade et al 2014), and elevated CO 2 resulted in increased levels of reproductive hormones in Atlantic cod (Preus-Olsen et al 2014). Together, these results suggest that stimulation of reproduction by elevated CO 2 could occur in a variety of fish species from a range of families.…”
Section: Reproductive and Offspring Characteristics: Cosupporting
confidence: 60%
“…In a previous experiment, Miller et al (2013) observed an increase in reproduction at elevated CO 2 levels similar to those used in this experiment. A similar increase in reproduction has since been documented in the three-spine stickleback (Schade et al 2014), and elevated CO 2 resulted in increased levels of reproductive hormones in Atlantic cod (Preus-Olsen et al 2014). Together, these results suggest that stimulation of reproduction by elevated CO 2 could occur in a variety of fish species from a range of families.…”
Section: Reproductive and Offspring Characteristics: Cosupporting
confidence: 60%
“…Conversely, proxies based on the analysis of mRNA expression are very useful to investigate the physiological impact of environmental cues on small organisms since they do not require a lot of biological material. Moreover, numerous studies demonstrated that OA-induced physiological disturbances were associated with regulation of gene expression (Cline et al, 2020, Frommel et al, 2020, Hamilton et al, 2017, Huth and Place, 2016, Lai et al, 2017, Mazurais et al, 2020a, Mazurais et al, 2020b, Shrivastava et al, 2019, Preus-Olsen et al, 2014, Tseng et al, 2013, Mittermayer et al, 2019, Michael et al, 2016. In particular, changes in mRNA levels of proteins involved in neural signalling processes have been observed in olfactory systems of fish exposed to OA (Williams et al, 2019, Porteus et al, 2018, including early stages of development (Rong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%